Facilitation of Bacterial Adaptation to Chlorothalonil-Contaminated Sites by Horizontal Transfer of the Chlorothalonil Hydrolytic Dehalogenase Gene - Liang, Bin (American Society for Microbiology, 2011)

(untitled)
Horizontal transfer of the chlorothalonil hydrolytic dehalogenase gene (chd) is proposed based on the high conservation of the chd gene and its close association with a novel insertion sequence, ISOcsp1, in 16 isolated chlorothalonil-dechlorinating strains belonging to eight different genera. The ecological role of horizontal gene transfer is assumed to facilitate bacterial adaptation to chlorothalonil-contaminated sites, through detoxification of chlorothalonil to less toxic 2,4,5-trichloro-6-hydroxybenzene-1,3-dicarbonitrile.